Pembangunan Kerangka Persekolahan Berasaskan Penjarakan Fizikal Pandemik Covid-19 - Mohd Nazri Abdul Rahman; Aminuddin Awang; Harry Tan Huat Hock; Muhammad Ridzuan Idris; Norazan Md Nor; Mohamed Shahren Abdullah; Azizan Puteh; Ng Weng Tutt (USIM Press, 2024)
Vol. 6 No. 2 (2021): Jurnal Sains Insani